Paragonimus kellicotti: A Lung Infection in Our Own Backyard - Eric Johannesen; Van Nguyen (Case Reports in Pathology)
Paragonimiasis is an infection caused by the lung fluke of the genus Paragonimus. Within the United States, paragonimiasis has been commonly diagnosed in Southeast Asian immigrants infected with the Asian lung fluke Paragonimus westermani. Infections from the North American lung fluke, Paragonimus kellicotti, have been rare, although more infections have been seen in people in the Midwestern United States. A 29-year-old male with a history of pleomorphic xanthoastrocytoma presented with hemoptysis. A CT scan showed a mass in the left upper lung lobe. A biopsy showed eosinophils and parasite eggs, some with a recognizable operculum. Further investigation revealed that he takes canoe trips on rivers within Missouri and would eat crayfish caught from these rivers. A blood sample was confirmed positive for Paragonimiasis serologically at the Center for Disease Control. Paragonimus kellicotti is found in rivers within the Mississippi basin. Infection occurs by consuming uncooked or undercooked crawfish. Microscopic identification of parasite eggs has been the gold standard. Serologic tests have been developed to aid in the diagnosis. Patients typically present with fever and hemoptysis. Common CT findings include pleural effusion, a mass, and lymphadenopathy. Awareness of P. kellicotti is important to guide appropriate diagnostic testing and ensuring proper treatment.